Smartphone‐based analysis of biochemical tests for health monitoring support at home. Issue 3 (23rd September 2014) - Velikova, Marina; Smeets, Ruben L.; van Scheltinga, Josien Terwisscha; Lucas, Peter J.F.; Spaanderman, Marc
Abstract : In the context of home‐based healthcare monitoring systems, it is desirable that the results obtained from biochemical tests – tests of various body fluids such as blood and urine – are objective and automatically generated to reduce the number of man‐made errors. The authors present the StripTest reader – an innovative smartphone‐based interpreter of biochemical tests based on paper‐based strip colour using image processing techniques. The working principles of the reader include image acquisition of the colour strip pads using the camera phone, analysing the images within the phone and comparing them with reference colours provided by the manufacturer to obtain the test result. The detection of kidney damage was used as a scenario to illustrate the application of, and test, the StripTest reader. An extensive evaluation using laboratory and human urine samples demonstrates the reader's accuracy and precision of detection, indicating the successful development of a cheap, mobile and smart reader for home‐monitoring of kidney functioning, which can facilitate the early detection of health problems and a timely treatment intervention.